Continuous Intraoperative Neuromonitoring Study Using Pigs for the Prevention of Mechanical Recurrent Laryngeal Nerve Injury in Esophageal Surgery. (April 2017) - Deguchi, Tomoaki; Ikeda, Yoshifumi; Niimi, Masanori; Fukushima, Ryoji; Kitajima, Masaki
Purposes . During esophageal surgery, clamping injury and injury associated with the use of energy devices are common mechanisms underlying intraoperative recurrent laryngeal nerve (RLN) damage. Recently, intraoperative neuromonitoring (IONM) has been applied to prevent RLN injury. This study was aimed at investigating the changes in the EMG signals associated with clamping injury of the RLN caused by picking up of the nerve with tweezers in domestic pigs. Methods . Six domestic pigs (12 RLNs) underwent continuous IONM (CIONM) by our original automated periodic vagal nerve stimulation method. Results . Our system can be used safely and accurately. The signals showed a decrease of the amplitude when the RLN was picked up and closed slowly by the double-action Maryland with jaw covers. If the clamp was released before the signal amplitude decreased to 50% of the baseline, the signal showed gradual recovery to the baseline in 12 ± 3 minutes. Conclusion . Although there were limitations in our study using domestic pig, including the small sample size, our results are expected to contribute to a decrease in the incidence of RLN damage during esophageal surgery.